BIOMASS AND CARBON FUELS IN METALLURGY - Legemza, Jaroslav (CRC Press, 2020)
Biomass and Carbon Fuels in Metallurgy presents contemporary and new insights into the use of carbonaceous (Biomass) fuels in the metallurgical sector. The authors describe application of these fuels in different technological processes to produce pig iron, steel and ferroalloys. Emphasis is placed on biomass and its metallurgical utilization. Coverage includes the specification of fuels, their classification and the characteristics of their basic properties. The use of carbonaceous fuels in the production of various kinds of agglomerates (ferriferous, manganese and metalized) is also covered. Key Features: Provides a comprehensive view of carbonaceous fuels in various metallurgy processes Details experiments conducted on the use of traditional and alternative (biomass) carbonaceous fuels for the production of agglomerates. Demonstrates that the energy potential of biomass can also be successfully used in pyrometallurgical processes Describes applications of biomass-based fuels in different technological processes for the production of pig iron, steel and ferroalloys. Coverage includes the specification of fuels, their classification and the characteristics of their basic properties.